The effect of weather variability on pediatric asthma admissions in Athens, Greece - Nastos, P. T.; Paliatsos, A. G.; Papadopoulos, M.; Bakoula, C.; Priftis, K. N. (Journal of Asthma, 2008)
The aim of this study was to determine whether there is any association between weather variability and asthma admissions among children in Athens, Greece. Medical data were obtained from hospital registries of the three main Children's Hospitals in Athens during the 1978-2000 period; children were classified into two age groups: 0-4 and 5-14 years. The application of Generalized Linear Models with Poisson distribution revealed a significant relationship among asthma hospitalizations and the investigated parameters, especially for the children aged 0-4 years. Our findings showed that Hospital admissions for childhood asthma in Athens, Greece, is negatively correlated with discomfort index, air temperature and absolute humidity whereas there is a positive correlation with cooling power, relative humidity and wind speed. Copyright © 2008 Informa Healthcare USA, Inc.
Keywords: Adolescent; air temperature; article; asthma; Athens; Child; child hospitalization; Child, Preschool; Childhood asthma; controlled study; cooling; correlation analysis; Generalized Linear Models; Greece; groups by age; hospital admission; human; Humans; humidity; linear system; major clinical study; parameter; Patient Admission; Poisson distribution; register; school child; seasonal variation; Weather; wind